Beliefs of Health Care Providers, Lay Health Care Providers and Lay Persons in Nigeria Regarding Hypertension. A Systematic Mixed Studies Review. - James Tosin Akinlua; Richard Meakin; Philip Fadahunsi; Nick Freemantle (PLoS ONE)
Background Hypertension is a major health risk factor for mortality globally, resulting in about 13% of deaths worldwide. In Nigeria, the high burden of hypertension remains an issue for urgent attention. The control of hypertension, among other factors, is strongly determined by personal beliefs about the illness and recommended treatment. Objective The aim of this review is to systematically synthesize available data from all types of studies on beliefs of the Nigerian populace about hypertension. Methods We searched the following electronic databases; Medline, EMBase, PsycInfo, AMED from their inception till date for all relevant articles. A modified Kleinman's explanatory model for hypertension was used as a framework for extraction of data on beliefs about hypertension. Results The search yielded a total of 3,794 hits from which 16 relevant studies (2 qualitative, 11 quantitative and 3 mixed methods studies) met the inclusion criteria for the review. Overall, most health care providers (HCPs) believe that stress is a major cause of hypertension. Furthermore, reported cut-off point for uncomplicated hypertension differed widely among HCPs. Lay Health Care Providers such as Patent Medicine Vendors' beliefs about hypertension seem to be relatively similar to health care professionals in areas of risk factors for hypertension, course of hypertension and methods of treatment. Among Lay persons, misconception about hypertension was quite high. Although some Nigerians believed that life style habits such as alcohol intake, exercise levels, cigarette smoking were risk factors for developing hypertension, there was discordance between belief and practice of control of risk factors. However, beliefs across numerous ethnic groups and settings (urban/rural) in Nigeria have not been explored. Conclusion In order to achieve control of hypertension in Nigeria, interventions should be informed, among other factors, by adequate knowledge of beliefs regarding hypertension across the numerous ethnic groups in Nigeria, settings (rural/urban), age and sex.